Adsorption and interaction of 2-aminopyridine with loughlinite (Na-sepiolite) from Anatolia - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (ASIAN JOURNAL OF CHEMISTRY, 11/100 RAJENDRA NAGAR, SECTOR 3,, SAHIBABAD 201 005, GHAZIABAD, INDIA, 2008)
FT-IR spectroscopy has been used to characterize adsorption and interaction of 2-aminopyridine by loughlinite, which belongs to palygorskite-sepiolite group of phyllosilicates class of clay minerals. The spectroscopic results indicate generation of 2-aminopyridinium cations. Cationic and neutral surface species adsorbed on loughlinite are coordinated to Bronsted acidic sites and surface hydroxyls (by H-bonding interaction through pyridine ring nitrogen lone pairs), respectively. It must be noted that the adsorption of 2-aminopyridine affected the hydroxyl group vibrations of loughlinite.
Keywords: adsorption; aminopyridine; clay minerals; IR spectroscopy; loughlinite; sepiolite; model-calculations; spectra; montmorillonite; intercalation; palygorskite; emme; aminopiridin; kil mineralleri; IR spektroskopisi; sepiyolit; model hesaplamaları